Pig production systems: biological, procedural, systemic and logistic approaches - Santos, Leandro Duarte dos; Mayerle, Sérgio Fernando; Rocha, Jhulielli; Rodriguez, Carlos Manuel Taboada (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The survey and knowledge of a production process, both by systemic perspective and logistics, can contribute significantly to management and consequently increase productivity and reduce costs. Based on a literature review and through the use of a systemic and logistic approach, the paper identifies the processes, inputs, outputs, activities and flows that are part of pig production and thus contributes to its economic, social and environmental development. Through a systemic approach of swine production, it is verified that the distance between the production site and the plantation of grain for swine feed supply influence economic and ecologic aspects. Hence, production sites near the plantation of grain provide competitive advantages. Based on this argument, a tendency for the migration of Brazilian swine production from the south region to the new frontier of MAPITOBA agriculture is verified. To mitigate the negative effects caused by this migration, technological, administrative and political measures have to be taken.